Effects of Nitrogen Fertilization on Soil CH4, CO2, and N2O Emissions and Their Global Warming Potential in Agricultural Peatlands - Yao Shi; Xiaowei Wei; Lianxi Sheng; Xuechen Yang (Agronomy)
Globally, 14–20% of peatlands are affected by agricultural activities, which account for about one-third of global greenhouse gas emissions from farmlands. However, how agricultural activities such as nitrogen fertilization affect peatlands’ CH4, CO2 and N2O emission patterns and their resulting warming effects needs to be improved and complemented. Here, we elucidate the characterization of CH4, CO2 and N2O emissions from the soil surface and different depths of the soil profile during the growing season of agricultural peatlands for over 50 years and the mechanisms of their resulting global warming potential (GWP) impact through field monitoring and molecular techniques. The 100-year GWP of peatlands increased by 1200% with N fertilization of 260 kg N ha−1 yr−1. At the soil surface, N fertilization increased CO2 and N2O emissions by 111% and 2600%, respectively, although CH4 emissions decreased by 87%. In the soil profile, N fertilization had a significant effect on CO2 from 0 to 60 cm, resulting in an increase in CO2 concentrations of 14–132%, whereas the top 30 cm of soil was the zone of significant N fertilization effects, with CH4 concentrations decreasing by 49–95% and N2O concentrations increasing by 22–26%. Elevated soil pH and NH4+ were the key environmental factors influencing CH4, CO2 and N2O emissions and their resulting increase in GWP. These results suggest that agricultural N fertilization led to a change in the contributor to the GWP of peatlands from CH4 to N2O, especially in the top 30 cm of soil. This study helps to provide theoretical support for the development of effective peatland management strategies.